Etc.: No End to Interpretation of Julien Green's Le Voyageur sur la terre - Robert Ziegler (Studies in 20th & 21st Century Literature, 1998)
A critical reappraisal of Julien Green's Le Voyageur sur la terre may bring a realization that the text itself is the itinerant traveler, a vagabond temporarily sheltered in readings accorded to it while it awaits entry into heaven, where its meaning is revealed. A tale incorporating inhospitable interpretations, Le Voyageur sur la terre charts a journey toward an impossible homecoming, where the confusion of narrative voices, origins, and identities is finally resolved in a celestial illumination of perfect clarity. As this paper argues, evidence of Green's protagonist Daniel O'Donovan's deliverance from the world is the exile of his narrative in the realm of incomprehension. What testifies to the integrity of the meaning of Green's story is the certainty that it cannot be grasped by confused and earthbound readers. The object of Green's Voyage is never to arrive but to pursue its endless journey through wrong interpretations, while maintaining a belief in a conclusive exegesis whose accuracy is a function of not being of this world.
Keywords: Julien Green; Le Voyageur sur la terre; itinerant traveler; vagabond; heaven; inhospitable; impossible homecoming; homecoming; narrative voices; origins; identities; Daniel O& #x27; Donovan; deliverance; exile; narrative; incomprehension; arrive; pursue; exegesis; interpretation